CURRENT SITUATION OF DEVELOPING SELF-AWARENESS SKILLS FOR CHILDREN WITH AUTISM SPECTRUM DISORDERS VIA ART THERAPY IN INCLUSIVE SCHOOLS (Proceedings of International Conference on Special Education, 2023)
Self-awareness is an important group of skills from the model of social-emotional learning which is extremely necessary for children. In this study, we present the result of a survey from 385 teachers at inclusive preschools and primary schools in Viet Nam on the development of self-awareness skills for children with ASD 4-8 years old via art therapy or art experience. The survey results show that some of the teachers are properly aware of the goal of developing self-awareness skills through art therapy for children with ASD 4-8 years old. The actual results also indicate some requirements for learning and teaching self-awareness skills through art therapy for children with ASD 4-8 years old. This result contributes to providing useful information in building a measure of self-awareness skills through art therapy for children with ASD 4-8 years old in inclusive schools in Vietnam. Art therapy can be an effective tool in developing self-awareness skills for children with ASD, in the condition that early intervention must be set up methodically and professionally. Finally, the role of teachers is a concern because they are the main in supporting children with special needs.